PENGARUH LINGKUNGAN KERJA FLEKSIBEL TERHADAP MOTIVASI KERJA KARYAWAN GEN Z DI PERUSAHAAN START-UP - Nazwa Sahara; Abdurohim (PT. Hasba Edukasi Mandiri, 2025)
As digital natives, Gen Z employees possess unique characteristics, including a strong affinity for technology, a desire for work-life balance, and a preference for flexibility in the workplace. A flexible work environment—which includes autonomy in choosing work time and location—has emerged as a relevant managerial approach to enhance productivity and job satisfaction among this generation. This research employs a quantitative approach using a survey method involving 100 Gen Z employees working in various startups across Indonesia. The data were analyzed using simple linear regression to examine the relationship between a flexible work environment and work motivation. The results indicate that a flexible work environment has a positive and significant impact on Gen Z employees' motivation. Flexibility fosters a sense of trust and autonomy, which in turn boosts enthusiasm and work loyalty.